Impact of the temporary suspension of the Bowel Screening Wales programme on inequalities during the COVID-19 pandemic: a retrospective register-based study. (November 2022) - Bright, Diana; Song, Jiao; Hillier, Sharon; Huws, Dyfed W; Greene, Giles; Hodgson, Karen; Akbari, Ashley; Griffiths, Rowena; Davies, Alisha R; Gjini, Ardiana
Abstract: Background: Response to the COVID-19 pandemic resulted in the temporary disruption of routine services in the UK National Health Service, including cancer screening. Following the reintroduction of services, we explored the impact on inequalities in uptake of the Bowel Screening Wales (BSW) programme to identify groups who might benefit from tailored intervention. Methods: BSW records were linked to electronic health record and administrative data within the Secured Anonymised Information Linkage (SAIL) Databank Trusted Research Environment. We examined uptake in the first 3 months (from August to October, 2020) of invitations following the reintroduction of the BSW programme compared with the same period in the preceding 3 years. We analysed inequalities in uptake by sex, age group, income deprivation quintile, urban and rural location, ethnic group, and uptake between different periods using logistic regression models. Findings: Overall uptake remained above the 60% Welsh standard during the COVID-19 pandemic period of 2020–21 but declined compared with the pre-pandemic period of 2019–20 (60·4% vs 62·7%; p<0·001). During the COVID-19 pandemic period of 2020–21, uptake declined for most demographic groups, except for older individuals (70–74 years) and those in the most deprived quintile. Variation by sex, age, income deprivation, and ethnic groups was observed in all periods studied. Among low-uptake groups, including males, younger individuals (60–64 years), those living in most deprived areas, and ethnic minorities, uptake remains below the 60% Welsh standard. Interpretation: Despite the disruption, uptake remained above the Welsh standard and inequalities did not worsen after the programme resumed activities. However, variations associated with sex, age, deprivation, and ethnicity remain. These findings need to be considered in targeting strategies to improve uptake and informed choice in colorectal cancer screening such as co-producing information products with low-uptake groups and upscaling the use of GP-endorsed invitations and reminder letters for bowel screening. Funding: Health Data Research UK, UK Medical Research Council, Administrative Data Research UK, and Health and Care Research Wales.